Analisis Kompetensi terhadap Kinerja Pegawai Universitas - Hafidzah Nurjannah (COSTING : Journal of Economic, Business and Accounting, 2019)
Performance in carrying out its functions does not stand alone, but is related to work ability and motivation. This study aims to determine how the influence of competencies (knowledge, skills, self-concept and value, and personal characteristics) on the performance of employees of the Islamic University of Riau. The population used in this study were all employees of the Islamic University of Riau, amounting to 130 people, while the sample method used in this study was the census method. After distributing questionnaires to 130 respondents but the questionnaire returned only 60 copies so that the sample in this study were 60 respondents. The results of this study indicate that the t test, namely knowledge, skills, self-concept and value, and personal characteristics have a positive and significant effect partially on the performance of UIR employees. The results of the analysis through the F test show that Knowledge, Skills, Self-concept and value, and Personal Characteristics have a positive and significant effect on the performance of UIR employees. Keywords: Knowledge, Skills, Self-concept and Value, Personal Characteristics, Employee Performance